Morphological analysis of Arabic-English intra-word code-switching on Facebook : free morpheme model - Eman Alamaren,; Shaidatul Akma Kasuma, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The main issue of the current study aims at analyzing the morphology of mixing bound and lexical morphemes from Arabic and English (intra-word code-switching), and finding out how this type of code-switching is performed. This study also examines the speakers’ maintenance of their Arabic morphological structure and word formation process while using English constituents. In order to meet the objectives of the study, the study employs qualitative approach. That is, the qualitative data are collected from Facebook conversations among Jordanian university students. Thematic analysis technique is used to provide morphological analysis of intra-word Arabic-English code-switching. Furthermore, clarification of some morphological differences between Arabic and English is provided along with analysis. Examples of intra-word codeswitching that are used in chats, comments, and posts on Facebook by Jordanian university students are investigated. The data analysis revealed that there are three patterns of intra-word code-switching; mixing between Arabic inflectional morphemes and English nouns, mixing between Arabic inflectional morphemes and English adjectives, and mixing between Arabic inflectional morphemes and English verbs. The results indicated that students do not use any English bound constituents with Arabic free morphemes. Moreover, the speakers ignore any grammatical demands of the inserted English verbs like present and past tense markers. Plus, the data revealed that the speakers perform intra-word code-switching within English nouns the most. In addition, Jordanian students maintained Arabic morphological rules without any violations while they are using English constituents. As a conclusion, code-mixing is frequently found within words and the study introduces a potential theoretical implication which is directed to the Arabic Language Academies in the Arab World. These Academic are responsible to coin appropriate Arabic words that meet the need of using English. Coining new Arabic words will limit using English within Arabic discourse, save Arabic purity, and enrich Arabic language with new terms. That is Arabic language have to have new lexicon to develop and stay alive.